HISTOMORPHOLOGY OF FEMALE ORGAN SYSTEM OF A NEMATODE OESOPHAGOSTOMUM COLUMBIANUM - JOHAL, MANJEET; JOSHI, ARCHNA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1994)
The telogonic ovary is enveloped by a thin epithelial layer and contains various stages of developing oocytes attached to a central cytoplasmirachis. Oviductis muscular and acts just as a passageway. The oviduct-uterincijunctionis consisted of large oval cells acting as a sphinctor. Anterior region of the uterus is modified to act as a fertilization chamber and is lined by a delicate membrane under the epithelium. Uterine epithelium of the mid region is secretory in nature and is responsible for the formation of the outerwall of the egg shell.